MEDIA IN DIGITAL AGE-REGULATORY ASPECTS - Mihajlov Prokopović, Anka M; Vujović, Marija (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The great influence of digital technology has led to a review of the concept of the media. In theory, agreement was reached on the new notion of media offered by Karol Jakubowicz (2009), which includes new content forms, new creators of content and new activities. The European regulatory framework, starting from this understanding of the media, redefines many earlier solutions in its documents. A significant change is the "broadening" of the media concept that now includes internet publications. On the other hand, editorial responsibility is a necessary condition for the website to be considered as a medium and this requirement is defined in European media policy documents. The challenges for media regulation are the phenomena created as a result of the new digital environment. The Internet has enabled the direct participation of citizens who set up online content using new distribution channels which, among other things, leads to a weakening of the borders between the public and private spheres. New intermediaries such as internet browsers and internet content aggregators, which perform some media functions and functions similar to the media, are entering the media sphere. The paper analyzes solutions offered by European as well as Serbian regulations in this field.